Relations with the Russian Federation in the programmes of selected Polish political parties: an outline of quatitative and qualitative analysys (Economic and Political Thought, 2018)
Particular political parties’ manifestoes constitute crucial elements ofpublic discourse. On the one hand, they are an emanation of the views heldby political parties and their voters, on the other hand, they form a basis forpolitical competition between particular formations, both during electoralcampaigns and in the periods between the elections. In the Polish politicalreality, proposals concerning foreign policy make one of pivotal elementsof those political programmes. The article aims to present the results ofthe research into the place of Russia and Polish-Russian relations in theprogrammes of the most important political formations operating in Poland.The author also attempts to review the political programmes for theirspecificity as well as their internal structures and the nature of the proposalsthat they include. As a result of the quantitative analysis, it has been concludedthat the relations with Russia constitute a crucial element in the politicalprogrammes proposed by the majority of significant Polish political parties.The qualitative analysis has made it possible to distinguish parties that call fora determined and assertive policy towards Russia, parties that formulate theirviews on Russia in a neutral way, as well as parties that call for improvementand pragmatism in bilateral Polish-Russian relations.
Keywords: political programmes, political parties, Polish-Russian relations